MOBILE HEALTH APPLICATIONS IN MANAGEMENT OF POLYCYSTIC OVARY SYNDROME (PCOS): A SYSTEMATIC REVIEW OF CLINICAL EFFICACY, QUALITY, AND SOCIO-ECONOMIC IMPLICATIONS - Maksymilian Głaz; Łukasz Deska; Szymon Zysiak; Dawid Głaz; Natalia Kamińska; Jędrzej Zaguła; Wojciech Sołtys; Cezary Kosmecki; Mateusz Stronczyński; Kacper Wicha (International Journal of Innovative Technologies in Social Science, 2026)
Background: Polycystic Ovary Syndrome (PCOS) constitutes the most prevalent endocrine disorder in reproductive-aged women, affecting approximately 8–13% of this population globally. Although lifestyle modification is the designated first-line therapy, adherence is frequently impeded by economic barriers and the lack of continuous, personalized support. Mobile health (mHealth) technologies propose a scalable solution to this "care gap," yet the digital marketplace remains fragmented, often lacking alignment between commercial usability and clinical evidence.Objectives: This systematic review evaluates the clinical efficacy, technical quality, and socio-economic implications of mHealth interventions in PCOS management to inform future clinical practice and reimbursement frameworks.Methods: A systematic search of academic databases covering the period from January 2010 to January 2025 yielded 34 eligible studies. These included Randomized Controlled Trials (RCTs) assessing clinical outcomes and content analyses utilizing the Mobile App Rating Scale (MARS).Results: Evidence from high-quality RCTs indicates that integrated mHealth interventions can function as effective "digital scaffolds" for behavioral change. Specific digital interventions demonstrated significant weight reduction (mean -3.19 kg) and improved insulin resistance with efficacy comparable to metformin. Furthermore, digital support significantly restored reproductive function, with long-term data showing a substantial increase in the prevalence of regular menstrual cycles, rising from 3.3% at baseline to 43.1% in intervention groups. However, technical analyses reveal a persistent "quality gap," where commercial applications prioritize aesthetics over evidence-based medical content.Conclusion: Mobile health applications represent a clinically valid and cost-effective adjunct to standard PCOS care. To realize their public health potential, future frameworks must bridge the divide between commercial user experience and academic rigor, ensuring equitable access to validated digital therapeutics.